Dynamic effects of personal initiative on engagement and exhaustion: The role of mood, autonomy, and support. (23rd March 2018) - Zacher, Hannes; Schmitt, Antje; Jimmieson, Nerina L.; Rudolph, Cort W.
Summary: Researchers have neglected dynamic effects of proactive behavior on occupational well‐being. We investigated effects of change in personal initiative over 6 months on changes in emotional engagement and exhaustion over the following 6 months. On the basis of the control‐process theory on affect, we hypothesized that changes in positive and negative moods mediate these effects conditional upon employees' level of perceived organizational support. On the basis of action regulation theory, we assumed that change in job autonomy also acts as a mediator. Data came from 297 employees who responded to 3 surveys separated by 6‐month intervals. Results of latent change score modeling showed that change in personal initiative negatively predicted change in positive mood and, when perceived organizational support was low, positively predicted change in negative mood. In addition, change in personal initiative positively predicted change in job autonomy. Change in personal initiative had negative indirect effects on change in emotional engagement, and positive indirect effects on change in emotional exhaustion through changes in positive and negative moods (but not through change in job autonomy). A reverse causal model did not yield significant indirect effects. Overall, these findings suggest that an increase in proactive behavior can have detrimental effects on occupational well‐being.